Efektivitas Program Jakarta Evolution (JakEVO) dalam Memberikan Pelayanan Perizinan di Jakarta Selatan - Rabbani Priyotomo; Khaerul Umam Noer (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
This study examines the effectiveness of the Jakarta Evolution (JakEVO) program in the implementation of online-based licensing services in South Jakarta, specifically for public transportation route licensing. The program was initiated as part of a public service reform effort aimed at improving accessibility, efficiency, and transparency in the licensing administration process. This study uses a qualitative descriptive approach with data collection techniques including in-depth interviews, field observations, and document studies, involving both the implementing officials at the South Jakarta UP PMPTSP and the public as service users. The findings indicate that JakEVO has positively contributed to the ease and flexibility of the licensing process, particularly in reducing the need for face-to-face interactions. However, its implementation has not yet been fully optimized due to several challenges, including limited program socialization, low digital literacy among the public, technical disruptions in the application system, and human resource capacity that is not fully adaptive to digital transformation. Additionally, the program's evaluation mechanism remains descriptive and lacks comprehensive quantitative performance indicators.